FORENSIC MEDICAL SIGNIFICANCE OF SUBSEQUENT ATROPHY IN OPTIC NERVE INJURY (Multidisciplinary Journal of Science and Technology, 2025)
Currently, optic nerve atrophy is not only a problem in modern ophthalmology related to the complexity of early differential diagnosis, severity of damage, and unfavorable prognosis, but also causes significant difficulties in forensic medical examination, including in determining the harm caused to health.